The effects of ball carrying on sprint mechanics: an insight into the technical demands of rugby - Brown, S. R.; Simperingham, K.; Morin, J.-B. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Sprinting ability is fundamental to success in rugby, where athletes are repetitively required to accelerate and occasionally reach maximal velocities while carrying a ball. Despite this, the mechanical influences of ball carrying are not understood. The aim of this study was to examine the effects of ball carrying technique on sprint performance and underlying mechanics. Sprint kinetics were collected with a radar gun on 16 male rugby athletes during three maximal 40-m sprints under three conditions: no ball, ball in two hands and ball in one hand. Carrying a ball in two hands produced similar mechanics to no ball over acceleration while carrying a ball in one hand had advantageous alterations at maximal velocity. A new sprint training protocol is proposed based on these findings.